Is There a Relationship Between Tic Frequency and Physiological Arousal? Examination in a Sample of Children With Co-Occurring Tic and Anxiety Disorders. (March 2014) - Conelea, Christine A.; Ramanujam, Krishnapriya; Walther, Michael R.; Freeman, Jennifer B.; Garcia, Abbe M.
Stress is the contextual variable most commonly implicated in tic exacerbations. However, research examining associations between tics, stressors, and the biological stress response has yielded mixed results. This study examined whether tics occur at a greater frequency during discrete periods of heightened physiological arousal. Children with co-occurring tic and anxiety disorders ( n = 8) completed two stress-induction tasks (discussion of family conflict, public speech). Observational (tic frequencies) and physiological (heart rate [HR]) data were synchronized using The Observer XT, and tic frequencies were compared across periods of high and low HR. Tic frequencies across the entire experiment did not increase during periods of higher HR. During the speech task, tic frequencies were significantly lower during periods of higher HR. Results suggest that tic exacerbations may not be associated with heightened physiological arousal and highlight the need for further tic research using integrated measurement of behavioral and biological processes.